2006
DOI: 10.1295/polymj.pj2006020
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Crystallization of Maleated Polypropylene/Graphite Flake Nanocomposites

Abstract: ABSTRACT:Polypropylene (PP)/graphite (G) hybrid nanocomposites have been prepared by melt mixing using maleated PP (PP-g-MA) and graphite oxide (GO) as compatibilizing agents. Melt mixing was achieved using a Gelimat, a high-speed thermo-kinetic mixer. The PP-g-MA and GO used as compatibilizers helped the dispersion of the graphite on a nano-scale and improved flexural properties but more significantly the impact strength of the material. TEM micrographs showed a partial exfoliation of the graphite in the PP/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…It can be seen from Table 4 that the addition of biofiber markedly reduced the activation energy for crystallization in pure PP. The low activation energy for crystallization obtained for the composites is consistent with their high crystallinity reported in Table 3, which could be attributed to the fact that biofibers, being high energy sites, lowered the activation energy for nucleation as similarly reported by Page & Gopakumar (2006). A close inspection of the data in Table 4 for the composites shows that at each level of fiber content, the application of MAPP increased their activation energy.…”
Section: Modeling Of Crystallizationsupporting
confidence: 86%
“…It can be seen from Table 4 that the addition of biofiber markedly reduced the activation energy for crystallization in pure PP. The low activation energy for crystallization obtained for the composites is consistent with their high crystallinity reported in Table 3, which could be attributed to the fact that biofibers, being high energy sites, lowered the activation energy for nucleation as similarly reported by Page & Gopakumar (2006). A close inspection of the data in Table 4 for the composites shows that at each level of fiber content, the application of MAPP increased their activation energy.…”
Section: Modeling Of Crystallizationsupporting
confidence: 86%
“…Gopakumar and Page [26,27] studied the effect of coupling agent (PP-g-MA) in PP/graphite nanocomposites and found that the addition of PP-g-MA in PP/graphite composites resulted an improvement in flexural properties and impact strength. In a recent study, Miquelard-Garnier and co-workers [28] used forced assembly through multilayer co-extrusion method to develop PMMA/PSgraphene and PMMA/PMMA-graphene systems and reported that the amount of reinforcement was greater than normally reported for graphene nanocomposites, due to the orientation of graphene in the direction of extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…Modification with maleic anhydride is commonly used for polyolefins to introduce hydrophilic groups into the originally hydrophobic matrix with the aim to improve the compatibility with hydrophilic fillers. 24 Obviously, maleic anhydride does not react covalently with graphene sheets of CNT, however, maleated polyolefins have much higher adhesion to the polar substrates than unmodified ones. 25 Therefore, improvements in the nanotube dispersion and adhesion between PP and CNT can be expected.…”
Section: Introductionmentioning
confidence: 99%